Hypomyelinating leukodystrophies: Translational research progress and prospects. Issue 1 (24th June 2014) - Pouwels, Petra J. W.; Vanderver, Adeline; Bernard, Genevieve; Wolf, Nicole I.; Dreha‐Kulczewksi, Steffi F.; Deoni, Sean C. L.; Bertini, Enrico; Kohlschütter, Alfried; Richardson, William; ffrench‐Constant, Charles; Köhler, Wolfgang; Rowitch, David; et al.
<x xml:space="preserve">Abstract</x> Hypomyelinating leukodystrophies represent a genetically heterogeneous but clinically overlapping group of heritable disorders. Current management approaches in the care of the patient with a hypomyelinating leukodystrophy include use of serial magnetic resonance imaging (MRI) to establish and monitor hypomyelination, molecular diagnostics to determine a specific etiology, and equally importantly, careful attention to neurologic complications over time. Emerging research in oligodendrocyte biology and neuroradiology with bedside applications may result in the possibility of clinical trials in the near term, yet there are significant gaps in knowledge in disease classification, characterization, and outcome measures in this group of disorders. Here we review the biological background of myelination, the clinical and genetic variability in hypomyelinating leukodystrophies, and the insights that can be obtained from current MRI techniques. In addition, we discuss ongoing research approaches to define potential outcome markers for future clinical trials. Ann Neurol 2014;76:5–19